Mechanical properties and microstructural evolution of FeNiCrCoCux high-entropy alloys: A molecular dynamics simulation - Cao, Yong; Liu, Junfeng; Zhou, Shengang; Xu, Yang (Solid state communications, 2023)
In this work, we used molecular dynamics simulations to research the relationship between mechanical properties and microstructural evolution in FeNiCrCoCux high-entropy alloys under uniaxial tension. The physical models were constructed based on the atomic simulations. We considered the influencing factors of Cu concentration (x = 0.1, 0.5, 1.0, 1.5, 2.0), temperature (300–1200 K) and strain rate (1 × 108–1 × 1011/s). The analysis of the results revealed multiple deformation mechanisms such as dislocation movement and shear strain. Both Cu concentration and temperature increase negatively affect the tensile properties of HEAs, including yield stress, yield strain, and Young's modulus. The dislocation density will thus decrease, and the shear strain will increase and become more uniform. The increase in strain rate increases the yield stress and yield strain of HEAs, while the change in Young's modulus is smaller and the dislocation density generally decreases. This work provides a microscopic understanding. We can design HEA with excellent mechanical properties by optimizing the material structure parameters of HEA. •High-entropy alloys are metal materials with better properties that have been studied in recent years, and there have been many achievements in experimental research on them.•However, through molecular dynamics simulation, a reference value and evolution law can be provided, which is more convenient for experimenters to find more excellent structural compositions.•This paper also refers to the results of previous studies for many times.